2022
DOI: 10.4143/crt.2021.890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen Receptor Expression Level and Hormonal Therapy on Prognosis of Early Breast Cancer

Abstract: Purpose Estrogen receptor (ER) expression in breast cancer plays an essential role in carcinogenesis and disease progression. Recently, tumors with low level (1%-10%) of ER expression have been separately defined as ER low positive (ER<sup>low</sup>). It is suggested that ER<sup>low</sup> tumors might be morphologically and behaviorally different from tumors with high ER expression (ERhigh).Materials and Methods Retrospective analysis of a prospective cohort database was performed. Pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…In the present study, ER low cases constituted 2% (46/2,309) of all IBC cases and 2.8% (46/1,666) of ER-positive IBC cases, which is consistent with previous studies that reported ER low cases accounted for 2%–5.1% of all IBC and 2.5%–7.4% of ER-positive IBC cases [ 6 7 9 13 14 15 ]. Some studies [ 9 13 ] have defined ER low as 1%–9% positive staining instead of 1%–10% (the ASCO/CAP definition). Furthermore, a recent study that used tissue microarray IHC data reported a slightly higher incidence of ER low cases (3% of all IBCs and 4.1% of ER-positive IBCs) [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, ER low cases constituted 2% (46/2,309) of all IBC cases and 2.8% (46/1,666) of ER-positive IBC cases, which is consistent with previous studies that reported ER low cases accounted for 2%–5.1% of all IBC and 2.5%–7.4% of ER-positive IBC cases [ 6 7 9 13 14 15 ]. Some studies [ 9 13 ] have defined ER low as 1%–9% positive staining instead of 1%–10% (the ASCO/CAP definition). Furthermore, a recent study that used tissue microarray IHC data reported a slightly higher incidence of ER low cases (3% of all IBCs and 4.1% of ER-positive IBCs) [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…Most ER low cases (93.5%) in the present study and > 50% of ER low cases in previous studies presented with low or negative PR expression [ 7 8 9 ], which may contribute to the lack of significant survival benefits of adjuvant hormone therapy for patients with ER low IBC. Previous studies have reported HER2 positivity in 29%–60% of ER low cases [ 7 8 9 ].…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations